ANALISIS PENERIMAAN PAJAK DAN PENGGUNA E-FILING PADA KANTOR PELAYANAN PAJAK PRATAMA KENDARI - Sitti Adehasmi; Rosnawintang Rosnawintang; La Ode Suriadi (JEP (Jurnal Ekonomi Pembangunan), 2021)
The purpose of this study is to analyze the effectiveness of the implementation of e-Filing taxes and tax receipts at the Kendari Pratama Tax Service Office from 2015-2019. The data used is secondary data. The analytical method to achieve the above objectives is to use the effectiveness formula with the help of effectiveness measurement criteria. The results of this study indicate that the target and realization of tax revenues in 2015-2019 has increased, but in 2017 there has been a decrease in the realization of tax revenues from Rp. 859,722,827,561 in 2016 to Rp. 823,398,282,149. In 2015-2018 the realization of tax revenue was lower than the target of tax revenue that had been set, in 2019 the realization of tax revenue exceeded the target of tax revenue that had been determined.Â  E-Filing users experienced a low increase from 2015-2019 both corporate taxpayers and individual taxpayers. This can be seen from the data on the number of e-Filing users every year which does not reach 10 percent of the total number of registered taxpayers at the Kendari Pratama Tax Service Office.